1976
DOI: 10.1159/000180585
|View full text |Cite
|
Sign up to set email alerts
|

Short Duration-High Area Regular Dialysis Using Two UF 2 Coils in Series

Abstract: To increase the number of regular dialysis patients without increasing apparatus, staff or buildings, short time-high area dialysis was undertaken for 3.5 h twice a week or 3 h three times a week with two UF 2 coils in series (2 m2) with dialysis fluid flow of 300 ml/min/kidney in parallel. The biochemical and clinical results were compared with those obtained in a period immediately prior to this using conventional 7-hours dialysis twice a week or 6 h three times a week on UF 145. Urea, creatinine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Economic incentives were demonstrated by early proponents of short dialysis. In the meantime, very efficient dialyzers had been designed and their values demonstrated in short-term studies [11,12] . Nevertheless, short-term studies would not be sufficient for the widespread use of short dialysis.…”
Section: Justification For Short Dialysismentioning
confidence: 99%
“…Economic incentives were demonstrated by early proponents of short dialysis. In the meantime, very efficient dialyzers had been designed and their values demonstrated in short-term studies [11,12] . Nevertheless, short-term studies would not be sufficient for the widespread use of short dialysis.…”
Section: Justification For Short Dialysismentioning
confidence: 99%
“…In the past, residual renal function was considered important for dialysis prescription . Twardowski reported that patients with urine output over 500 mL/24 hours could achieve clinically adequate dialysis in 12 hours per treatment based on twice‐weekly schedule; however, patients with lower urine output required three or more dialysis per week .…”
Section: Residual Renal Functionmentioning
confidence: 99%
“…In the past, residual renal function was considered important for dialysis prescription. 38,39 Twardowski reported that patients with urine output over 500 mL/24 hours could achieve clinically adequate dialysis in 12 hours per treatment based on twice-weekly schedule; however, patients with lower urine output required three or more dialysis per week. 23 The residual renal function measured by creatinine clearance was also correlated with clinical status in patients dialyzed twice weekly for 12 hours in each session, but the correlation was inferior to that found for simple urine output.…”
Section: Residual Renal Functionmentioning
confidence: 99%
“…Barth [7] argued that at least three factors were necessary to make it possible: technical feasibility, economic incentives, and medical/scientific justification. Ari et al [9] compared 7-hr dialysis twice weekly or 6-hr thrice weekly dialysis on a UF 145 with 3.5-hr twice a week or 3-hr three times a week with two UF 2 coils in series (2 m 2 ), respectively. Shortly thereafter, more efficient dialyzers were designed.…”
Section: Justification For Short Dialysismentioning
confidence: 99%
“…Additionally, more efficient coil and parallel plate dialyzers were devel-oped in the early 1970s, so removal of uremic toxins seemed to be possible in short-duration dialysis. Ari et al [9] compared 7-hr dialysis twice weekly or 6-hr thrice weekly dialysis on a UF 145 with 3.5-hr twice a week or 3-hr three times a week with two UF 2 coils in series (2 m 2 ), respectively. They found no differences between the pairs.…”
Section: Justification For Short Dialysismentioning
confidence: 99%